Screening of cytokines in blood serum and lacrimal liquid in wet and atrophic forms of age-related macular degeneration - V. V. Neroev; N. V. Balatskaya; N. V. Neroeva; A. G. Karmokova; M. V. Ryabina; I. G. Kulikova (Медицинская иммунология)
Cytokines play an integral role in pathogenesis of age-related macular degeneration (AMD). Of particular interest are the late stages of this disease, which causes progressive visual impairment. Therapy-induced effects of post-treatment cytokine concentrations also need to be studied, both at long and short observation terms. These studies are of vital importance if the atrophy occurs during antiangiogenic therapy. Our purpose was to study an array of 45 cytokines, in blood serum (BS) and lacrimal liquid (LL) of the patients with wet and atrophic AMD.The study included 70 people (85 eyes) with stage 3-4 AMD according to AREDS. Depending on the form of AMD, 3 groups were discerned: I group (n = 24) included the patients with “geographic atrophy”; II group (n = 22), consisted of the patients with macular atrophy treated with antiangiogenic therapy of wet AMD; III group (n = 24), comprised the patients with a wet AMD who did not previously receive the treatment. Control group consisted of healthy volunteers (n = 25). All the groups were comparable for age and gender. The patients underwent a comprehensive ophthalmological examination to make a diagnosis. A multiplex study of the local (in the BS) and systemic (in the LL) cytokine status was carried out on a MAGPIX device (platform хMAP, Luminex Corporation, USA) in the Luminexx PONENT 3.1 software, using Procarta Plex kits (eBioscience, Austria). We determined 45 cytokines causing various biological effects, i.e., IL-1á, IL-1â, IL-1ra, IL-2, IL-4, IL-5, IL-6, IL-7, IL-9, IL-10, IL-12p70, IL-13, IL-15, IL-17A, IL-18, IL-21, IL-22, IL-23, IL-27, IL-31, IFNá, IFNã, IL-8/CXCL8, IP-10/CXCL10, SDF-1á/CXCL12, MCP-1/CCL2, MIP-1á/CCL3, MIP-1â/ CCL4, RANTES/CCL5, Eotaxin/CCL11, TNFá, TNFâ, GM-CSF, VEGF-A, VEGF-D, FGF-2, EGF, PDGF-BB, HGF, SCF, GRO-á, NGF-â, BDNF, LIF, PIGF-1.Screening of a wide range of cytokines showing various biological effects was carried out in BS and LL of patients with atrophic and wet forms of AMD. It has been shown that the late stages of the disease are associated with local and systemic changes of pro / anti-inflammatory mediators (IL-1â, IL-1ra, IL-18, LIF), chemoattractant cytokines (IL-8/CXCL8, IP-10/CXCL10, MCP-1/CCL2, MIP-1á/CCL3, MIP-1â/ CCL4, RANTES/CCL5, Eotaxin/CCL11), hematopoietic regulators (IL-7), and growth factors with known angiogenic activity (EGF, HGF, PDGF-BB, VEGF-A). Altered concentrations of numerous chemokines, e.g., IP-10/CXCL10, SDF-1á/CXCL12, MIP-1á/CCL3, MIP-1â/CCL4, RANTES/CCL5 and Eotaxin/CCL11 (p < 0.05) in BS of the patients with atrophic and wet AMD may be of interest for the search of biomarkers associated with various clinical phenotypes of the disease and may be also helpful for development of new therapeutic strategies.